The Maternal–Fetal Gut Microbiota Axis: Physiological Changes, Dietary Influence, and Modulation Possibilities - Eva Miko; Andras Csaszar; Jozsef Bodis; Kalman Kovacs (Life, 2022)
The prenatal period and the first years of life have a significant impact on the health issues and life quality of an individual. The appropriate development of the immune system and the central nervous system are thought to be major critical determining events. In parallel to these, establishing an early intestinal microbiota community is another important factor for future well-being interfering with prenatal and postnatal developmental processes. This review aims at summarizing the main characteristics of maternal gut microbiota and its possible transmission to the offspring, thereby affecting fetal and/or neonatal development and health. Since maternal dietary factors are potential modulators of the maternal–fetal microbiota axis, we will outline current knowledge on the impact of certain diets, nutritional factors, and nutritional modulators during pregnancy on offspring’s microbiota and health.